"There Is Always an Excuse to Blame the Girl": Perspectives on Sexual Harassment at a Jordanian University. (November 2022) - Bergenfeld, Irina; Clark, Cari Jo; Sandhu, Seema; Yount, Kathryn M.; Essaid, Aida A.; Sajdi, Jude; Abu Taleb, Rand; Robbin, Zoe; Batayeh, Brian; Zwooqar, Ahad; Spencer, Rachael A.
Sexual harassment (SH), defined as unwelcome conduct of a sexual nature, presents a global public health issue and a barrier to empowerment for women and girls. To understand the perceived causes of SH in the Jordanian university context, we conducted focus groups ( n  = 6) and participatory data collection with students ( n  = 317) and interviews with staff and administrators ( n  = 5) at a public university. These data identified norms governing men's and women's behavior, institutional climate and policies, tribal conservatism and protection of perpetrators, and early socialization as underlying SH. Campus-based interventions should adopt approaches aimed at multiple levels of the social ecology.